2008
DOI: 10.21273/horttech.18.4.563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flowering and Foliage Plants in Hospital Rooms on Patients Recovering from Abdominal Surgery

Abstract: Using various medical and psychological measurements, this study performed a randomized clinical trial with surgical patients to evaluate if plants in hospital rooms have therapeutic influences. Ninety patients recovering from an appendectomy were randomly assigned to hospital rooms with or without plants. Patients in the plant treatment room viewed eight species of foliage and flowering plants during their postoperative recovery periods. Data collected for each patient included length of hospitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 24 publications
3
69
1
6
Order By: Relevance
“…Flowering plants and foliage in hospital rooms have attributed to enhanced recovery rates of patients undergoing appendectomies (Park and Mattson, 2008, 2009a). Patients in rooms with flowers and plants required less post-operative medications, demonstrated more positive physiological responses (heart rate, anxiety and fatigue, lower systolic blood pressure, pain ratings) and had more positive emotions and greater satisfaction with their hospital rooms than those in the control group.…”
Section: Physical and Mental Health Disordersmentioning
confidence: 99%
“…Flowering plants and foliage in hospital rooms have attributed to enhanced recovery rates of patients undergoing appendectomies (Park and Mattson, 2008, 2009a). Patients in rooms with flowers and plants required less post-operative medications, demonstrated more positive physiological responses (heart rate, anxiety and fatigue, lower systolic blood pressure, pain ratings) and had more positive emotions and greater satisfaction with their hospital rooms than those in the control group.…”
Section: Physical and Mental Health Disordersmentioning
confidence: 99%
“…Patients in hospital rooms with plants and flowers needed significantly fewer postoperative analgesics; had reduced systolic blood pressure and heart rate; lower ratings of pain, anxiety, and fatigue; and had more positive feelings than patients in the control group. 11 Men are usually the givers rather than the receivers of flowers, but sometimes a stay in hospital is a good excuse to reciprocate. Haviland-Jones et al found that flowers have immediate and long term effects on emotional reactions, mood, social behaviours, and memory for men and women alike.…”
Section: Brightening Effectmentioning
confidence: 99%
“…In Barker, Rasmussen and Best's (2003) study it was shown that when comparing patients attending electroconvulsive therapy in a room, either with or without a fish tank, a trend toward a lower level of anxiety was found in the group of patients who had the fish tank compared with those patients who did not. But animals do not seem to be the only living beings that have such effects, as plants also show an anxietyalleviation effect in patients recovering from surgery (Park and Mattson 2008).…”
mentioning
confidence: 99%
“…Due to their relatively unproblematic keeping and handling, we studied the effect of a dog and a fish-animals that have already been shown to have a positive impact on humans' emotions. Given that plants have an anxietyreducing effect on patients recovering from surgery (Park and Mattson 2008), we compared the effect of the aforementioned animals with the effect of a plant (Ficus benjamina), one of the Anxiety-Reducing Effect: Dog, Fish and Plant in Direct Comparison…”
mentioning
confidence: 99%